The Effect of (M.I.T) Strategy on the Achievement of Second-Grade Female Students of Intermediate School in the Arabic Language Subject (International Journal of Psychosocial Rehabilitation, 2020)
The research was conducted in Iraq, which aimed to know "the impact of (M.I.T) strategy on the achievement of second-grade female students of Intermediate school in the Arabic language", the researcher followed the experimental approach as it was the suitable approach to the current research, the research community was the intermediate d high school for girls in the center of Hilla in the province of Babylon, she chose one of the intermediate schools, as a research sample of (78) students, (40) students of the experimental group and (38) students of the control group, chose the research tool was as an achievement test for the Arabic grammar, and the research experiment was carried out by the same researcher for a full semester of the academic year (2019 - 2020). The researcher used the statistical package (SPSS) in the use of the T-test, the Chi-square, and the Pearson correlation coefficient in the research procedures and reached the results; the results showed the superiority of the experimental group over the control group.